Cumulus-oocyte developmental competence: From morphological selection to molecular markers - Nasser Ghanem; Romysa Samy; Dalia Abd-El Rahman Ahmed; Beshoy SF Khalil; Eman Kh Kassab; Md Fakruzzamana; Kong IK (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
The intrinsic quality of mammalian cumulus-oocyte complexes (COCs) is a determinant factor for pregnancy and fertility in general. The efficiency of assisted reproductive techniques required selection of good quality COCs. Despite the efforts that has been made during the last decades until now worldwide, there is no a reliable non-invasive method or even a reliable marker for oocyte selection. Generally, oocyte quality evaluated based on its morphological features such as thickness, compactness of the cumulus investment and the homogeneity of the ooplasm, which is relatively popular and convenient. However, results derived from this tool are often conflicting largely due to subjectivity and inaccuracy. Thus, the morphological evaluation alone is insufficient to distinguish competent oocytes that have the ability to bring about full-term pregnancy. Biochemical constituents of the follicular fluid represent sensors of the microenvironment condition surrounding the oocyte. Few efforts have given an attention for follicular fluid to be used as oocyte biomarker. Noteworthy, intensive application of assisted reproductive biotechnologies in human and domestic animal species require a good method for selecting good quality oocytes. Recently, global assessment strategies of omics approaches (transcriptomics, miRNAomics, proteomics, lipidomics and metabolomics) have been applied to profile the follicular fluid, oocytes, and granulosa or cumulus cells in several animal species in addition to human. Integration of more than one tool could be a window for finding reliable judging method. Although the great contribution of oocyte quality in controlling fertility the efforts done in finding reliable biological markers is still in the infancy stage. The current short review will shed highlight on attempts has been made in this field.